Peran Manajemen Inovasi dalam Mendorong Pertumbuhan Ekonomi Masyarakat - Fitriani Fajar; Delyana Rahmawany Pulungan; Eva Yuniarti Utami; Nurjanna Ladjin; Krisna Meidiyantoro B. (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the elements in increasing the country's economic growth is measured by the country's ability to innovate. This is because innovation can encourage sustainable productivity increases that can increase economic growth. This study aims to determine the role of management innovation in encouraging community economic growth. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that management innovation plays an important role in encouraging community economic growth, these roles include increasing productivity and efficiency, creating jobs, encouraging economic growth, killing and managing resources, and resilience and adaptation. There are two things that are the benchmarks for the success of an innovation, namely Technical resources (human, equipment, knowledge, and financial), and Ability (capability/ability of the country to manage resources at the point of technical resources